Prevalence and factors affecting food insecurity among university students in Pahang, Malaysia - Mohd Abu Bakar, Wan Azdie; Ismail, Shahidah; Sidek, Suriati; Abdul Rahman, Rozlin (Nutrition Society of Malaysia, 2019)
Introduction: Food insecurity exists whenever people are unable to access sufficient food at all times for an active and healthy life. University students are a potentially vulnerable group of people to face food insecurity. This study aimed to identify the prevalence and determinants of food insecurity among a population of university students in Kuantan, in the state of Pahang. Methods: Food security status was identified using the United States Adult Food Security Survey Module (USAFSSM). Factors, which include demographic background, spending expenditure pattern and time constraints, were assessed. A total of 316 students were selected through stratified random sampling throughout six faculties of the International Islamic University Malaysia, of whom 307 successfully completed the survey. Results: The result shows that 54.4% of the students were experiencing food insecurity, from which 32.9% were sub-categorised as low food security and 21.5% as very low food security. Food insecurity was found to be significantly associated with time constraints (p<0.05), spending on books (p<0.05), miscellaneous items (p<0.05), parents’ income (p<0.001) and scholarship type (p<0.001). Conclusion: Apart from the high incidence of food insecurity among the students, time and financial affordability appeared to be critical concerns in this study. Since food insecurity has become a significant issue with university students, it should be addressed and prioritised by the relevant authorities.